2020
DOI: 10.15419/bmrat.v7i9.633
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth and low birth weight in neonates with postnatal respiratory failure at a tertiary hospital in Viet Nam

Abstract: Introduction: This study aimed to evaluate the rate of preterm birth and low birth weight in neonates having postnatal respiratory failure. Methods: A cross-sectional design was used in the study. There were 139 neonates with postnatal respiratory failure and 278 neonates without respiratory failure included in the study. Data on comorbidities, gestational age, and mechanical ventilation status were collected. Results: Among neonates with respiratory failure, the rate of preterm birth (< 37 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Being born extremely very low and very LBW increases the hazard of RDS among LBW neonates. This finding is supported by different studies conducted in China,49 Indonesia,54 Vietnam55 and Saudi Arabia 2. The possible justification for this is a lack of surfactant caused by lung immaturity is one example of the physiological and anatomical immaturities that can occur in newborns who have LBW 56.…”
Section: Discussionmentioning
confidence: 62%
“…Being born extremely very low and very LBW increases the hazard of RDS among LBW neonates. This finding is supported by different studies conducted in China,49 Indonesia,54 Vietnam55 and Saudi Arabia 2. The possible justification for this is a lack of surfactant caused by lung immaturity is one example of the physiological and anatomical immaturities that can occur in newborns who have LBW 56.…”
Section: Discussionmentioning
confidence: 62%
“…10 This conformed to the study in Vietnam which found that children with a birth weight below the standard could cause heart failure, and might need hospital admission due to the severity of the disease. 30 To clarify, the disease commonly found in children with a history of birth weight below the standard is an abnormal respiratory system. It also conformed to the study on the relationship between low birth weight and acute respiratory infection in Telaga Health Care Clinic Gorontalo District, which found that both were significantly related to each other.…”
Section: Discussionmentioning
confidence: 99%
“…All infants with RDS have lower birth weight than infants without RDS (64.8%). A study by Nam et al,. showed that infants with low birth weight (< 2500 gram) are more likely to get respiratory failure (Nam et al, 2020).…”
Section: Discussionmentioning
confidence: 99%